Aplicación de la técnica Mapas Mentales para mejorar la Comprensión Lectora en los estudiantes del 2° “a” de Educación Secundaria en la I.E N°80824 “José Carlos Mariátegui” en El Porvenir - Barreto Pérez, Liliana (2017)
This research work has the purpose of applying the technique of the mind map for improving reading comprehension in students of 2° "A" of the I.E. N°80824 "José Carlos Mariátegui" in the future. _x000D_ The population was 228 students and the sample was composed of 32 students who have applied the measuring instruments._x000D_ The procedures used were those that the statistics provides us, beginning with the construction of tables, graphs, and application of the statistical test of comparison of hypotheses to approve research hypotheses._x000D_ It was determined in the students, that the 56.3 % of them obtained a satisfactory level in the posttest after the application of the technique of the mind map, as well as the 65.6% of students achieved a satisfactory level in the literal dimension; the 59.4% of the students obtained a process level in the dimension inference and 93.8% of them obtained a satisfactory level criticism at the posttest; determining, finally, that there is a significant difference between the scores obtained in the posttest with those obtained in the pretest in reading comprehension of students ( p < 0.05), as a result of the application of the technique of mental maps . The same situation occurred in the dimensions: literal, inferential and critical reading comprehension (p < 0.05)._x000D_ It was concluded that the application of the technique of mental maps significantly improves reading comprehension in students of 2° "A" of Secondary Education of the I.E. N° 80824 "José Carlos Mariátegui" in the future.